Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conserva tion goals. One approach that shows considerable promise for addressin g these challenges is adaptive management, which by now is broadly see n as a natural, intuitive, and potentially effective way to address de cision-making in the face of uncertainties. Yet the concept of adaptiv e management continues to evolve, and its record of success remains li mited. In this article, we present an operational framework for adapti ve decision-making, and describe the challenges and opportunities in a pplying it to real-world problems. We discuss the key elements require d for adaptive decision-making, and their integration into an iterativ e process that highlights and distinguishes technical and social learn ing. We illustrate the elements and processes of the framework with so me successful on-the-ground examples of natural resource management. F inally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and str ategic challenges.
Keywords: IMPORTANT